Tough choices: the experience of family members of critically ill patients participating in ECMO treatment decision-making: a descriptive qualitative study - Xiangying Yang; Yao Lin; Amao Tang; Xiaokang Zeng; Weiying Dai; Qian Zhang; Li Ning (BMC Medical Informatics and Decision Making)
Abstract Background ECMO treatment for critically ill patients mostly requires family members to make surrogate decisions. However, the process and experience of family members’ participation in decision making have not been well described. Purpose To explore the experience of family members of critically ill patients who were asked to consent to ECMO treatment and to gain insight into the factors that promote and hinder their decision-making. Methods A descriptive qualitative study. Data were collected using a semi-structured interview method and analysed using traditional content analysis approaches. The cohort included nineteen family members of critically ill ICU patients from a general hospital in China. Results Eleven family members consented to ECMO treatment, and 8 refused. 4 themes and 10 subthemes emerged: (1) tough choices: the dilemma in the emergency situation, the guilt and remorse after giving up; (2) rationalisation of decision-making: ethics and morality guide decision-making, expected efficacy influences decision making, and past experience promotes decision making; (3) decision-making methods: independent decision-making, group decision-making, decision making based on patient preferences; (4) influencing factors of decision making: information and communication, social support. Conclusion The findings provide insights and a basis for promoting efficient ECMO decision-making in clinical practice. It may be difficult to improve the time it takes to make the decision without sacrificing the quality of the decision. Healthcare professionals should provide timely emotional support, informational support, and comprehensive social support to assist them in making efficient decisions while respecting the treatment preferences of the decision-makers.